Autophagy in ischemic stroke: role of circular RNAs - Yiting Hong; Liyuan Gu; Bing Han; Honghong Yao (Open Exploration Publishing Inc., 2023)
Stroke, a central nervous system (CNS) injury, is responsible for the second leading cause of death in the world, bringing a great burden on the world. Stroke is normally divided into ischemic and hemorrhagic stroke, among which ischemic stroke takes up 87% proportion. Accumulating evidence has denoted a rather pivotal role for autophagy in the pathogenesis of ischemic stroke, which is activated in neuronal cells, glial cells, and endothelial cells. Besides, circular RNAs (circRNAs), a novel type of epigenetic regulation, are highly expressed in the CNS and are involved in the process of CNS diseases, which is regarded as an important molecular mechanism in ischemic stroke. Meanwhile, circRNA and autophagy have a significant correlation. The intracellular signaling pathways regulating autophagy can either restrain or activate autophagy. However, under the circumstances of ischemic stroke, the precise communication between circRNA and stroke is largely unknown. This review aims to provide a summary of the relationship between circRNA, autophagy, and ischemic stroke, as well as the current research advancements in understanding how circRNA regulates autophagy in the context of stroke.